STUDENT ATTITUDE TOWARD CONNECTING STRATEGY IN READING - Indah Purnamasari; Salmiati Kudadiri; Emeliya Sukma Dara Damanik (Yavana Bhasha : Journal of English Language Education, 2022)
Reading is one of the most important thing in this whole world. Researchers have become increasingly interested in children’s motivation to read. Because reading is an exigent activity that involves choice, motivation is crucial to reading engagement. Besides, reading is not just for reading, but also to increase our knowledges about everything that is very important to everyone and ourselves to make a better world with reading, not just in mind but also for attitude. The purpose of this case study was to investigate student attitude toward connecting strategy in reading at the student in Department of English State Islamic University of North Sumatera in the third semester. It was hypothesized that students attitude would improve during their literacy in school and everywhere they doing their activities about reading. Students attitudes were assessed through an onlline interview using platform Google Form as one of the most common tools for doing miniresearch in this pandemic era of the Covid-19. Findings indicated that reading consistent involvement in the learning process was crucial for students success. Furthermore, students attitude toward connecting strategy were found to be multidimensioanl and challenging to assess.